(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: This study aims to formulate and evaluate synthetic anti-dandruff shampoo. Materials and Methods: The anti-dandruff agents used in the present study are sulfur and benzoic acid. The other ingredients include sodium lauryl sulfate (surfactant), urea (solubilizing agent), citric acid (sequestering agent), sodium ethylenediaminetetraacetic acid (chelating agent), guar gum (foam stabilizing agent and thickening agent), tween 80, and distilled water (vehicle). All ingredients were purchased from SD fine chemicals, boisar. Results and Discussions: The prepared anti-dandruff shampoo was evaluated for physical appearance/visual inspection, determination if pH, determine % of solid contents, rheological evaluation, surface tension measurement, foam ability, and antimicrobial activity. The pH range was 6.1–6.7, physical appearance was pale yellow, the percentage of solid contents ranges from 26.9 to 28.1%, viscosity was in the range of 1289–1712, surface tension was found to be 31.08–34.12, and foam volume ranges from 144 to 178. The antimicrobial activity was done using Staphylococcus aureus, and the zone of inhibition was observed using 1% solution of sulfur, salicylic acid, and benzoic acid in the ratio of 0.75:2:0.25, which has shown 3.4 mm inhibitory action.Conclusion: Study indicates zone of inhibition for F1 obtained was best compared to other formulations against S. aureus after incubating for 24 h. It may have fair anti-dandruff activity efficiency.